One Ring to Rule Them All? : New Evidence on World Cycles - Monnet, Eric (IMF Working Papers; Working Paper ;, 2019)
We estimate world cycles using a new quarterly dataset of output, credit and asset prices assembled using IMF archives and covering a large set of advanced and emerging economies since 1950. World cycles, both real and financial, exist and are generally driven by US shocks. But their impact is modest for most countries. The global financial cycle is also much weaker when looking at credit rather than asset prices. We also challenge the view that syncronization has increased over time. Although this is true for prices (goods and assets), this not true for quantities (output and credit). The world business and credit cycles were as strong during Bretton Woods (1950-1972) as during the Globalization period (1984-2006). For most countries, the way their output co-moves with the rest of the world has changed little over the last 70 years. We discuss the reasons behind these new findings and their policy implications for small open economies.